Customer relationship management. Strategy and system perspectives - Czopek, Miłosz; Kazusek, Marta (Zarządzanie relacjami z klientem. Strategia i perspektywy systemowe, 2020)
Market dynamics, growing consumer awareness, new needs, and the changing lifestyle of society forces the search for new business solutions. One of them is the strategy known as Customer Relationship Management, CRM, i.e. customer relationship management interpreted as a bridge between the organization and its customers. Its goal is to establish lasting and long-term ties between the organization and buyers, which translate into benefits for both parties. The term CRM is interpreted in two ways: as a customer relationship management strategy and as an IT system. The aim of this article is to discuss the most important aspects of customer relationship management, both from the perspective of management philosophy and a technical support instrument. The article shows the sources of strategies and technical solutions, definitions, benefits resulting from the implementation of CRM in organizations, functions of CRM systems, application possibilities, and individual stages of implementation
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 3 (57), s. 34-48
Keywords: customer relationship management; customer loyalty; enterprise management; customer satisfaction; zarządzanie relacjami z klientem; lojalność klientów; zarządzanie przedsiębiorstwem; sytysfakcja klientów